Assessment of respiratory and ion transport potential of Penaeus japonicus gills in response to environmental pollution - ABDEL-MOHSEN, H.A. (Mediterranean Marine Science, 2009)
The present study aims to pinpoint the respiratory and ion transport potential of gills of Penaeus japonicus living in Abu-Qir Bay, East of Alexandria, Egypt. Our results revealed clear histological impairments in gill structure. These alterations were mainly represented by the presence of large vacuoles in gill axis and gill lamellae. In addition, narrow, disrupted gill lamellae with wavy cuticle and shrunk pillar cells were detected. Moreover, some cells clearly showed pyknosis. Gill ultrastructure also showed abnormal chromatin condensation inside the nucleus. Obvious alterations in the typical shape and structure of mitochondria were observed. Noticeably, the main characteristics of ion regulating gill epithelium were absent thus suggesting a low ion transport activity of P. japonicus gills. Statistically, this was further proved by the significantly higher activity levels of respiratory enzymes, namely, lactate dehydrogenase (LDH) and succinate dehydrogenase (SDH) compared to those of the ion transport enzymes, namely, adenosine triphosphatase (ATPase) and carbonic anhydrase (CA) in gills and haemolymph. SDH activity levels were higher than the corresponding levels of LDH in gills and its own level in haemolymph, indicating a contradictory effect of pollution on respiratory enzyme activity levels.